Pengaruh Kompensasi, Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan melalui Kepuasan Kerja - Ayu Lestari; Tedi Rusman; Albet Maydiantoro (FKIP Universitas Lampung, 2020)
This study aims to determine the effect of compensation, work discipline and work motivation on employee performance through job satisfaction. The population in this study is the employee of PT. Federal International Finance Bandar Lampung in 2019-2020. In this study a population of 50 people was used. Determination of the sample is done using probability sampling using the simple random sampling method. Then the number of samples obtained in this study amounted to 44 people. Data collection was carried out using a questionnaire. The analysis technique uses the Linear Regression Hypothesis Testing with Path Analysis. The research method used in this research is descriptive verification method with ex post facto and survey approaches. The result of this study indicate that there is a significant effect on compensation, work discipline and work motivation on employee performance through job satisfaction of employees of PT. Federal International Finance at 95%.Keywords : Compensation, Work Discipline, Work Motivation, Employee Performance, Job Satisfaction, Employees, PT. Federal International Financehttp://dx.doi.org/10.23960/E3J/v3i2.pp69-80